Senior and junior rugby league players improve lower-body strength and power differently during a rugby league season - Wade, J. A.; Fuller, J. T.; Devlin, P. J.; Doyle, T. L. (The Journal of Strength and Conditioning Research, 2022)
This investigation evaluated lower-body strength and power changes across a rugby league season in elite junior and senior athletes. Twenty-five senior and 20 junior rugby league players performed an isometric midthigh pull and countermovement jump at 3 time points in a National Rugby League training season (mid-preseason, end-preseason, and in-season). Linear fixed-effects models were used to compare isometric midthigh pull force and countermovement jump power between player experience groups (senior vs. junior) across the season phases (mid-preseason vs. end-preseason vs. and in-season). Cohen's effect sizes (ES) with 95% confidence intervals were calculated for pairwise comparisons. For senior players, absolute and relative strength (ES = 0.38, p < 0.007) and power (ES = 0.64, p < 0.008) increases were observed at end-preseason compared with mid-preseason, but there were no changes in-season (ES = 0.02, p > 0.571). For junior players, strength did not change (ES < 0.01, p > 0.738) and absolute power decreased (ES = 0.29, p < 0.014) at end-preseason compared with mid-preseason; large increases were evident for absolute and relative strength (ES = 1.43, p < 0.001) and power (ES = 0.62, p < 0.001) in-season. This research demonstrates senior and junior rugby league players exhibit unique patterns of improvements in lower-body strength and power across different phases of the season. This highlights the importance for training programs to differ between junior and senior athletes and target different physical qualities for both groups at different times of the season, thus providing guidance for strength and conditioning coaches.